Not War, Not Peace? : Motivating Pakistan to Prevent Cross-Border Terrorism - Perkovich, George and Dalton, Toby (India Oxford University Press, 2016)
India confronts an exceptionally difficult national security problem: how to motivate Pakistan to prevent cross-border terrorism. 'Not War, Not Peace?' examines India's options in developing an effective strategy. Drawing on extensive interviews with senior serving and retired Indian and Pakistani officials, it provides rigorous analysis of India's options to motivate Pakistan's behaviour while staying left of nuclear boom.
Include Index
Keywords: Terrorism--Prevention -- Pakistan -- India